158k views
2 votes
If f(x)=2x(With an exponent of 2) -3, find f(-2)


f\left(x\right)=2x^2-3f ( x ) = 2 x 2 − 3 find f\left(-2\right)f ( − 2 ).

User Penleychan
by
5.8k points

2 Answers

7 votes

Answer:

f(-2) = 5

Explanation:

We just need to substitute x with -2 and simplify.

f(x) = 2x² - 3

f(-2) = 2(-2)² - 3

f(-2) = 2(4) - 3

f(-2) = 8 - 3

f(-2) = 5

Best of Luck!

User Peeja
by
5.1k points
6 votes

Answer:

5

Explanation:

Put -2 where x is and do the arithmetic.

f(x) = 2x² -3

f(-2) = 2(-2)² -3 = 2(-2)(-2) -3 = 8 -3

f(-2) = 5

User John Corry
by
5.3k points